METODE HARUM PALA (Hafalan Rumus Pakai Lagu) PADA MATERI SEGITIGA DAN SEGIEMPAT - Ryan Angga Pratama; Rahayu Sri Waskitoningtyas; Besse Intan Permatasari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This research objective to develops and produce learning method in Triangle and Rectangle material. The research method using Research and Development (R & D) Design with ADDIE model which involves steps: Analysis, Design, Development, Implementation, and Evaluation. In its implementation, HARUM PALA (Memorize Formulas Using Songs) method was first validated by 1 learning strategy expert, 3 material experts, and 3 practitioners/teachers, which was later revised and implemented in SMP Negeri 4 Balikpapan, SMP Negeri 7 Balikpapan, and SMP Patra Dharma 2 Balikpapan. The methods used in data collection are interviews, documentation, and questionnaires. In this research, the feasibility of the learning strategy expert was obtained with a percentage of 85.45% (feasible), material experts with an average percentage of 85% (feasible), and practitioners / teachers at an average percentage of 84% (feasible). Based on the achievement of student learning, the average student in the Small Scale Trial of 69.78 and on the Large Scale Test of 75.34. So, as a whole, the product of the learning method HARUM PALA (Hafalan Rumus Pakai Lagu) can be said to be feasible to be used as a method of junior high school mathematics learning.